Comparison between anal cytology, high-resolution anoscopy and HPV DNA genotyping by polymerase chain reaction in the post-treatment follow-up of condylomata acuminata - NADAL,LUIS ROBERTO (2020)
ABSTRACT Aim: to evaluate the presence of subclinical HPV-induced anal lesions with anal cytology, High-Resolution Anoscopy (HRA) and HPV genotyping by polymerase chain reaction (PCR) in the follow-up of treated condylomata acuminata (CA). Methods: seventy-nine male patients were included. One month after anal CA eradication, the patients underwent brush samples collection for anal cytology and PCR, and HRA with biopsy of acetowhite lesions. These methods were compared within all patients and between groups, according to Human Immunodeficiency Virus (HIV) infection status: HIV-negative; HIV-positive with TCD4 count above and below 350 cells/mm3. Results: the most frequent HPV types were 6 and 16. HPV DNA was isolated in 92%. HIV infection was associated with a higher number of oncogenic HPV types (p=0.038). All patients with negative PCR had negative HRA and cytology. There were no differences in cytological, HRA or histopathological findings between groups. Conclusion: the association of the findings of cytopathology, HRA and genotyping of HPV refined the diagnosis of HPV-induced lesions. The degree of immunodeficiency was not associated with increase in remnant HPV-induced anal lesions.